Comparative Study of Urinary Albumin Excretion in Pre-Eclamptic Women in Different Duration (Bangladesh Medical Journal, 2014)
Pre-eclampsia is one of the important causes of maternal death in developing countries like Bangladesh. The analysis of 24 hour urine for protein excretion remains the best method of monitoring proteinuria in pregnancy. 24 hour urine collection is notoriously difficult to obtain when repeated analysis is needed in pre-eclamptic women .With this back ground, this study was carried out in BSMMU and DMCH from November 2004 to January 2005 to determine whether 12 hours urine collection for measuring albumin excretion in pre-eclamptic women can be a substitute for 24 hour collection. This study was performed on 40 women with pre-eclampsia who were admitted to the hospital. In each patient urinary albumin concentrations in two 12 hours samples (12 hour day and 12 hours night samples) were measured against the standard 24-hour albumin excretion. It was found that albumin concentrations in the 12-hour day and 12-hours night collections were close to the concentrations of the 24-hour collection. DOI: http://dx.doi.org/10.3329/bmj.v40i3.18672 Bangladesh Medical Journal 2011 Vol.40(3):33-36